Colossal Capacity Loss during Calendar Aging of Zn Battery Chemistries - Liu, Bo; Yuan, Xintong; Li, Yuzhang (Meeting abstracts (Electrochemical Society), 2024)
Whereas previous research efforts in Zn battery chemistries have primarily focused on extending their cycle life, calendar aging has largely been neglected and is poorly understood. Here, we discover that Zn metal anodes lose 12-37% of their capacity after only 24 hours of calendar aging, which is more than an order of magnitude greater than any other battery chemistry previously studied. We find that this large capacity loss occurs regardless of electrolyte chemistry, substrate composition, and calendar aging time, suggesting that the losses cannot be accounted for by corrosion alone. By leveraging titration gas chromatography, we distinguish corrosion losses from losses due to electrically disconnected Zn ("dead" Zn) and quantify dead Zn as the main contributor to capacity loss during Zn battery aging. More broadly, this study shows that large instabilities in seemingly non-reactive metals (e.g., Zn) can occur, highlighting the importance of understanding their underlying degradation mechanisms. Figure 1